Association Between Spirituality and Cybersex Behavior Among Twelfth-Grade Adolescents: A Cross-Sectional Study in Surabaya Indonesia - Fatimawati, Iis; Arini, Diyah; Faridah, Faridah; Darso, Andreas Alfa Bramantio (Journal of Applied Nursing and Health, 2026)
Background: Despite increasing internet-related sexual activities among adolescents, evidence regarding the role of spirituality in preventing cybersex behavior remains limited, particularly in Surabaya Indonesia; therefore, this study examined the relationship between spirituality level and cybersex behavior among twelfth-grade adolescents. Methods: A cross-sectional study following STROBE guidelines was conducted among 108 twelfth-grade students at ITP High School Surabaya, selected through simple random sampling from a population of 148. Inclusion criteria were active twelfth-grade students consenting to participate, while exclusion criteria were incomplete questionnaires or absence due to illness. The independent variable was spirituality level, and the dependent variable was cybersex behavior. Data were collected using the Daily Spiritual Experience Scale (DSES) and Internet Sex Screening Test (ISST). Ethical clearance was obtained from the Ethics Committee of Hang Tuah Health Sciences Institute (PE/90/VII/2024/KEP/SHT), and data were analyzed using Spearman’s rho correlation. Results: Univariate analysis showed that 61.1% of respondents exhibited moderate spirituality and 66.7% were classified as at-risk cybersex users. Bivariate statistical analysis revealed a significant moderate negative correlation between spirituality level and cybersex behavior (Spearman’s rho ρ = 0.001, r = -0.310, 95% CI [-0.473, -0.128).. Conclusion: Higher spirituality is significantly associated with lower cybersex behavior among adolescents, suggesting that internal spiritual experiences serve as an essential protective factor. It is recommended that school nurses and educators design spirituality-integrated digital literacy interventions.